2014
DOI: 10.1371/journal.pone.0104013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Air Pollutants and Economic Development of the Provincial Capital Cities in China during the Past Decade

Abstract: With the economic development of China, air pollutants are also growing rapidly in recent decades, especially in big cities of the country. To understand the relationship between economic condition and air pollutants in big cities, we analysed the socioeconomic indictorssuch as Gross Regional Product per capita (GRP per capita), the concentration of air pollutants (PM10, SO2, NO2) and the air pollution index (API) from 2003 to 2012 in 31 provincial capitals of mainland China. The three main industries had a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 69 publications
2
30
0
1
Order By: Relevance
“…China's most populous megacities, Shanghai and Beijing, are expected to increase from 23.7 to 30.8 million and from 20.4 to 27.7 million, respectively, between 2015 and 2030 [2]. The relationship between economic development and air quality in China's largest cities has followed the inverted-U shape of an environmental Kuznets curve for the past several decades [36], with pollution-related mortality highest in the megacities of Beijing, Shanghai, and the Pearl River area [5••].…”
Section: Chinamentioning
confidence: 99%
“…China's most populous megacities, Shanghai and Beijing, are expected to increase from 23.7 to 30.8 million and from 20.4 to 27.7 million, respectively, between 2015 and 2030 [2]. The relationship between economic development and air quality in China's largest cities has followed the inverted-U shape of an environmental Kuznets curve for the past several decades [36], with pollution-related mortality highest in the megacities of Beijing, Shanghai, and the Pearl River area [5••].…”
Section: Chinamentioning
confidence: 99%
“…, Egli , Roca et al . , Cai Zhonghua , and Yunpeng Luo found that only few relationships between environmental degradation and economic output supported the EKC hypothesis. Moreover, the fulfillment of the hypothesis was mostly conditional.…”
Section: Introductionmentioning
confidence: 96%
“…However, some practitioners addressed that the inverted Ushaped relationship did not always exist. Jie He and Patrick Richard, [15], Song et al [16], Egli [17], Roca et al [18], Cai Zhonghua [19], and Yunpeng Luo [20] found that only few relationships between environmental degradation and economic output supported the EKC hypothesis. Moreover, the fulfillment of the hypothesis was mostly conditional.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of N compounds from the atmosphere goes under a fusion process occurring between the gas particles or particulates and precipitation molecules as the result of collision and coalescence processes, as well as in-cloud and below-cloud scavenging processes, during precipitation's entire lifetime (Franklin, 2014;Jung et al, 2003;Murillo et al, 2012). Various factors influencing these processes have been investigated in detailed (i) characteristic of precipitation, for example, intensity (Elperin et al, 2016;Jung et al, 2003), rainfall rate (Ferm, 1998;Hannemann et al, 1996), raindrop size (Ebert et al, 1998;Jung et al, 2003), and ice particles properties (Jin & Chu, 2007); (ii) characteristics of the constituents, for example, chemistry (Fuzzi et al, 1994, Behera et al, 2013, emission (Fagerli & Aas, 2008;Luo et al, 2014), and daily fluxes (Rubio et al, 2002); and (iii) meteorological condition, for example, atmospheric circulation and air temperature (Hongisto & Joffre, 2005;Murillo et al, 2012). Pools and fluxes of different N-species via atmospheric precipitation have been also explored: below-cloud scavenging of HNO 3 and NO 3 during rainfall (Calderón et al, 2008); heterogeneous formation processes influence on NO 2 concentration in atmospheric liquid phase (Acker et al, 2008); in-cloud multiphase distribution of NH 3 /NH 4 + , HNO 3 /NO 3 -, and HNO 2 /NO 2 - (Fuzzi et al, 1994); SO 2 /NH 3 /CO 2 plume uptake versus raindrop size (Hannemann et al, 1996); and fluxes of NO, NO 2 , HONO, HNO 3 , NH 3 , NH 4 + , and NO 3 in the atmosphere (Trebs et al, 2006).…”
Section: Introductionmentioning
confidence: 99%